Processo de implantação do quadro de gestão à vista: um estudo de caso - Santos, Tawana Oliveira (2017)
In the pursuit of increased productivity, improved quality and reduced costs, companies call for continuous improvement. One of the ways to solve the problem is through cash management. It can present important information for the activities that will be carried out by that sector or process and expose the production data so that everyone has easy access to the information. Knowing this importance, this article had to present the implementation of the cash management system in a factory in the state of Sergipe. Through it there was an increase in productivity and a greater commitment of the employees in the achievement of goals.